Quality Control in Indonesia's Coconut Supply Chain - Ikatrinasari, Zulfa Fitri; Rais, Suyoto; Pambengkas, Rahid; Alfa, Bonitasari Nurul (Jurnal Agro Industri Perkebunan, 2026)
Indonesia holds the largest coconut plantation area globally, accounting for 3.37 million hectares or 31.2% of the world’s total. Despite being the top exporter of fresh coconuts in shells, valued at USD 56 million, the country’s coconut exports still have low added value. This study aims to identify the structure and quality control mechanisms of the coconut supply chain in Riau and propose recommendations for improvement. The research employed field surveys involving stakeholders across the supply chain to assess current quality control practices. The supply chain begins with farmers and collectors, leading to either the copra industry (30%) or the coconut processing industry (70%), then to the crude coconut oil (CCO) industry as an intermediate stage. After refining, this becomes Coconut Oil (CNO), which is distributed to the food (38%) and non-food sectors. Quality control practices include sorting coconuts into standard and non-standard categories at the farmer level, and classifying copra into edible (15%), regular (60%), and rejected (25%) types at the copra industry level. The study recommends formalizing coconut classification standards, ensuring copra is free from aflatoxin contamination, and increasing the added value of non-standard coconuts through downstream innovations such as Sustainable Aviation Fuel (SAF). These measures are expected to enhance product quality, support industrial diversification, and strengthen Indonesia’s position in the global coconut market.